2020
DOI: 10.1002/cbic.202000600
|View full text |Cite
|
Sign up to set email alerts
|

Metal Ion Promiscuity and Structure of 2,3‐Dihydroxybenzoic Acid Decarboxylase of Aspergillus oryzae

Abstract: Broad substrate tolerance and excellent regioselectivity, as well as independence from sensitive cofactors have established benzoic acid decarboxylases from microbial sources as efficient biocatalysts. Robustness under process conditions makes them particularly attractive for preparative‐scale applications. The divalent metal‐dependent enzymes are capable of catalyzing the reversible non‐oxidative (de)carboxylation of a variety of electron‐rich (hetero)aromatic substrates analogously to the chemical Kolbe‐Schm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 42 publications
(31 reference statements)
2
31
0
Order By: Relevance
“…11 kcal/mol. This approximation has been applied in all the studies presented here and has been shown to yield satisfactory results [44] , [45] , [46] , [54] .…”
Section: Computational Methodsologymentioning
confidence: 92%
See 3 more Smart Citations
“…11 kcal/mol. This approximation has been applied in all the studies presented here and has been shown to yield satisfactory results [44] , [45] , [46] , [54] .…”
Section: Computational Methodsologymentioning
confidence: 92%
“…Interestingly, Zn was initially proposed to be the divalent metal ion commonly adopted by AHS decarboxylases [33] , [35] , [42] , but Mn was recently determined to be the catalytic metal in LigW [43] , γ-RSD [44] and IDCase [45] . 2,3-DHBD has been shown to be active with both Mn and Mg [46] .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several decarboxylases employ divalent metal ions without requiring any organic cofactors. For example, 2,6‐dihydroxybenzoic acid decarboxylases (2,6‐DHBDs) [48] and 2, 3‐DHBDs [49] utilize Zn 2+ and Mg 2+ /Mn 2+ respectively to facilitate the carboxylation of dihydroxybenzenes, while the aliphatic carboxylase, phosphoenolpyruvate carboxylase (PEPC) [50,51] employs either Co 2+ , Mg 2+ , or Mn 2+. in its carboxylation process.…”
Section: An Overview Of Synthetically Targeted (De)carboxylasesmentioning
confidence: 99%